2004
DOI: 10.1002/ana.20032
|View full text |Cite
|
Sign up to set email alerts
|

Localization of white matter volume increase in autism and developmental language disorder

Abstract: Increased brain volume in autism appears to be driven mainly by an unexplained white matter enlargement, and we have reported a similar phenomenon in developmental language disorder (DLD). Localization of this enlargement would strongly guide research into its cause, tissue basis, and functional implications. We utilized a white matter parcellation technique that divides cerebral white matter into an outer zone containing the radiate compartment and an inner zone containing sagittal and bridging system compart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
402
4
9

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 603 publications
(451 citation statements)
references
References 38 publications
34
402
4
9
Order By: Relevance
“…Although we did not predict group differences in head circumference in this older sample of children with HFA (see Herbert et al 2004), it was hypothesized that there may be an atypical relation between the early component/peak amplitude of the MRP and head circumference for the HFA group.…”
mentioning
confidence: 57%
“…Although we did not predict group differences in head circumference in this older sample of children with HFA (see Herbert et al 2004), it was hypothesized that there may be an atypical relation between the early component/peak amplitude of the MRP and head circumference for the HFA group.…”
mentioning
confidence: 57%
“…While most human sutures do not close until adulthood, the metopic, or frontal suture, closes by approximately age two (Cohen, 1993). Several authors have reported that the regions with the most abnormally increased volume in autism are frontal gray and white matter (Carper and Courchesne, 2005;Carper et al, 2002;Herbert et al, 2004). The regional reduction in the volume of the frontal horn of the left ventricle (and the strong trend to a regional reduction in the right frontal ventricular volume) could therefore be a reflection of excessive frontal growth.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the increased cortical volumes described in children with autism. MRI studies have shown that the increased brain volumes in children with autism are to a large degree the result of increased white matter volumes [6,[56][57][58]. Using MRI-base morphometric analysis Herbert and colleagues [57] report disproportionately larger cerebral white matter volumes in boys with autism.…”
Section: Discussionmentioning
confidence: 99%
“…Using MRI-base morphometric analysis Herbert and colleagues [57] report disproportionately larger cerebral white matter volumes in boys with autism. They have gone on to localize the increased white matter volume to later or longer-myelinating regions of the radiate white matter compartment to all cerebral lobes (frontal, parietal, temporal and occipital) [58]. Akshoomoff et al [1] showed that in very young children with autism, variations in cerebral and cerebellar volumes, particularly white matter volumes, are correlated with diagnostic and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation